2018
DOI: 10.1016/j.tox.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapeutic drugs on the CYP1A1-catalysed metabolism of the environmental carcinogen benzo[a]pyrene: Effects in human colorectal HCT116 TP53(+/+), TP53(+/−) and TP53(−/−) cells

Abstract: Polycyclic aromatic hydrocarbons such as benzo[a]pyrene (BaP) can induce cytochrome P450 1A1 (CYP1A1) via a p53-dependent mechanism. The effect of different p53-activating chemotherapeutic drugs on CYP1A1 expression, and the resultant effect on BaP metabolism, was investigated in a panel of isogenic human colorectal HCT116 cells with differing TP53 status. Cells that were TP53(+/+), TP53(+/-) or TP53(-/-) were treated for up to 48 h with 60 μM cisplatin, 50 μM etoposide or 5 μM ellipticine, each of which cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…In HCT116 cells, p53-mediated induction of CYP1A1 was observed after treatment with PAHs such as BaP, DBA, and DBP (Wohak et al 2016). When studying several chemotherapeutic drugs, it was found that etoposide and ellipticine induced CYP1A1 in HCT116 TP53(+/+) cells, but not in HCT116 TP53(−/−), demonstrating that the mechanism of CYP1A1 induction was p53-dependent, whereas cisplatin had no such effects (Willis et al 2018). In the present study, 1-HMP treatment did not result in the induction of SULT1A1/3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HCT116 cells, p53-mediated induction of CYP1A1 was observed after treatment with PAHs such as BaP, DBA, and DBP (Wohak et al 2016). When studying several chemotherapeutic drugs, it was found that etoposide and ellipticine induced CYP1A1 in HCT116 TP53(+/+) cells, but not in HCT116 TP53(−/−), demonstrating that the mechanism of CYP1A1 induction was p53-dependent, whereas cisplatin had no such effects (Willis et al 2018). In the present study, 1-HMP treatment did not result in the induction of SULT1A1/3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of p53 in DNA damage response, new functions are still being discovered. Over recent years, a role for p53 in modulating carcinogen metabolism has emerged Simoes et al 2008;Krais et al 2016a;Krais et al 2016b;Wohak et al 2016;Willis et al 2018;Wohak et al 2018). We have shown that DNA adduct formation by BaP was significantly impacted by p53 function both in vitro and in vivo and that the observed DNA damage correlates with CYP1A1 expression (Krais et al 2016a;Wohak et al 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…HCT116 TP53(+/+ ), TP53(+/− ), TP53(−/− ), TP53(R248W/+ ) and TP53(R248W/− ) cells were treated with 1 µM 3-NBA, 10 µM 3-ABA, 1 µM N -OH-3-ABA or DMSO alone (control) for 48 h and whole cell lysates were analysed for the expression of p53 and p21 by western blotting. Both proteins have been shown to be sensitive markers to assess DNA damage response in HCT116 cells ( 23 , 39 ). As seen in Figure 4 , treatment with 3-NBA resulted in strong induction of p53 in TP53(+/+ ), TP53(R248W/+ ) and TP53(R248W/− ) cells whereas 3-ABA and N -OH-3-ABA induced p53 to a lesser extent in these cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the lower band is assumed to be nonspecific. The antibody has been shown to be sensitive to detect human CYP1A1 protein in cultured human cells (including HCT116) exposed to BaP ( 23 , 39–41 ). However, in this study CYP1A1 protein expression after 3-NBA, 3-ABA and N -OH-ABA exposure was weak or hardly detectable ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%